2021
DOI: 10.3390/ijerph18115650
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use of Prescription Skin Lightening Creams

Abstract: The desire for an even skin tone pervades all cultures and regions of the world. Uniform skin color is considered a sign of beauty and youth. Pigmentation abnormalities can arise idiopathically with genetic predetermination, with injury and environmental exposures, and with advancing age, and can, therefore, be distressing to patients, leading them to seek a variety of treatments with professional assistance. In this short report, we describe the trends in the use of prescription lightening creams, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Skin pigmentation regulators include melanocytes in the epidermis that synthesize melanin, and keratinocytes that receive and distribute it in upper layers of the skin [6]. Other factors that may affect pigment cell function and proliferation and create alterations in pigmentation include fibroblasts in the dermis, endocrine factors, blood supply, neural factors, inflammation mediators, ultraviolet radiation, genetics, and skin injury [7]. Common types of hyperpigmentation are lentigines, melasma, and postinflammatory hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Skin pigmentation regulators include melanocytes in the epidermis that synthesize melanin, and keratinocytes that receive and distribute it in upper layers of the skin [6]. Other factors that may affect pigment cell function and proliferation and create alterations in pigmentation include fibroblasts in the dermis, endocrine factors, blood supply, neural factors, inflammation mediators, ultraviolet radiation, genetics, and skin injury [7]. Common types of hyperpigmentation are lentigines, melasma, and postinflammatory hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…F I G U R E 3 Forest plots showing the comparison of the Melasma Area and Severity Index (MASI)/ modified MASI (mMASI) score changes in patients receiving 1064QNYL combined therapy compared with 1064QNYL alone at treatment endpoint, 4 weeks and 8 weeks after treatment hypermelanosis usually appear in long-term use. 22 Tranexamic acid is frequently used in melasma treatment recently, with good efficacy. However, the risk of thrombosis could be troublesome in the long term.…”
Section: Publication Biasmentioning
confidence: 99%
“…Several reports have shown that HQ might be related to damage to renal and liver cells [22][23][24]. Moreover, there are concerns related to possible carcinogenicity induced by HQ [25]. Thus, the usage of HQ as a cosmetic additive is prohibited in various places, such as Australia, the UK, Europe, Asia, and Africa [26,27].…”
Section: Introductionmentioning
confidence: 99%